Primary Care for the Poor : The Potential of Micro-Health Markets to Improve Care - Coarasa, Jorge (2016)
Much of the primary curative care provided to the poor by the private sector occurs not at large hospitals but at small, single-person clinics. While such micro-health providers increase access, questions persist about quality. Some have argued that the micro-health sector needs to be better regulated. This note cites recent studies in arguing that the micro-health sector needs to be better understood. A more evidence based approach may enable the World Bank Group to better target investments and interventions and help these providers fulfill an important role serving the poor. The following recommendations are made at the conclusion of this paper: (1) Effort, rather than hardware or training, may count the most. (2) Scaling up interventions to improve quality requires understanding and addressing market failures. (3) Changing the way impacts are measured will lead to smarter investments.